Elevated IL-6/IL-1Ra ratio as a prognostic biomarker of poor chemotherapy efficacy in Chinese patients with metastatic NSCLC, validated in a Caucasian patient cohort - Liu, Fang (Mol Clin Oncol, 2019)
The treatment options for advanced (stage IV) non-small cell lung cancer (NSCLC) at diagnosis remain disappointing. The development of immunotherapeutic drugs may represent a promising alternative approach to the treatment of late-stage cancer at diagnosis. These current paradigms in cancer treatment highlight the need for new biomarkers related to the immune status of the patients and/or the tumor microenvironment, for immune as well as chemotherapeutic treatment options. The aim of the present study was to analyze soluble immune factors in patients with lung cancer treated with chemotherapy to identify prognostic biomarkers. For this purpose, the data obtained from two cohorts of patients from different clinical trials were analyzed: A Chinese patient cohort to identify potential prognostic biomarkers, and a validation cohort comprising patients with a similar clinical stage from a clinical trial in Europe. Analyses of soluble markers for inflammation and immune status were performed by standard assays and multiplex Luminex assays. Differences in overall survival (OS) and progression-free survival (PFS) were evaluated with the log-rank test and robustness was evaluated with the resampling approach. In the Chinese cohort, four prognostic biomarkers of poor response to chemotherapy were identified, which had a significant impact on OS and PFS. It was confirmed in the Caucasian validation cohort that an increased value of the interleukin (IL)-6/IL-1Ra cytokine ratio at inclusion was correlated with significantly shorter OS and PFS, whereas no other biomarkers were found to be significant. The IL-6/IL-1Ra ratio reflects the imbalance between pro- and anti-inflammatory status in the plasma of patients and may be associated with tumor inflammatory status and the therapeutic outcome. The present study highlights the identification of the IL-6/IL-1Ra ratio as a biomarker of poor prognosis in terms of response to chemotherapy in two independent clinical studies.